Governance for the environment a comparative analysis of environmental policy integration - Goria, Alessandra; Sgobbi, Alessandra; Homeyer, Ingmar von.; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub. Ltd., 2010)
The integration of environmental concerns into other policy areas is widely recognized as a key element to achieve sustainable development. It also represents a challenge for the environmental community, requiring not only a new approach to policy-making but also changes to existing policies and their implementation. This essential book presents a diverse set of perspectives and experiences on how to support sustainable development through the integration of environmental issues into various policy sectors.
1. Insights from environmental economics in the integration of environmental policy into decision-making / Frank J. Convery -- 2. Environmental policy integration and the nation state : what can we learn from current practices? / Alessandra Sgobbi -- 3. Environmental policy integration at the regional and local levels : setting the problem into context / Michela Catenacci -- 4. The transformations of regional and local governments : implications for environmental policy integration / Bruno Dente -- 5. Sustainability and environmental policy integration : local level sustainability through knowledge involvement and new governance arrangements / Georgios Terizakis -- 6. From G-FORS to EPIGOV : which. governance modes for EPI? : the case of strategic environmental assessment in spatial planning / Carolina Pacchi and Davide Zanoni -- 7. A systems theoretical perspective on greening EU regional policy / Philipp Schepelmann -- 8. Environmental policy integration in the UK / Duncan Russel and Andrew Jordan -- 9. The case of EPI in Central and Eastern Europe / Keti Medarova-Bergström, Tamara Steger and Adam Paulsen -- 10. EPI and regional governance in Spain / Josu Mezo and Kenneth Hanf.
Includes bibliographical references and index.
Keywords: Environmental policy; Electronic books